NAVIGATING THE NEW NORMAL: A PRACTICAL GUIDE TO POST-PANDEMIC HR POLICIES - Tuti Damayanti; Ramon Zamora; Lukmanul Hakim (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The COVID-19 pandemic precipitated a permanent transformation in the global workplace, shifting employee expectations toward flexibility, well-being, and purpose. This has created a critical misalignment with traditional, office-centric HR policies, leading to risks of attrition, inequity, and disengagement. This article aims to develop a practical framework for redesigning HR policies to meet the demands of the post-pandemic "new normal." Utilizing an integrative review methodology, it synthesizes contemporary academic and industry literature to formulate actionable guidance. The results and discussion are structured around five pillars: implementing structured hybrid work models, intentionally cultivating culture in a dispersed environment, embedding holistic well-being into operations, and transforming talent management for equity and agility. The conclusion argues that a proactive, integrated approach to these areas is not an administrative task but a strategic imperative. Organizations that successfully adapt their people’s practices by fostering trust, inclusivity, and resilience will secure a sustainable competitive advantage in the evolving landscape of work.